2014
DOI: 10.4103/0970-1591.142078
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in robotic radical prostatectomy: Outcomes and management

Abstract: Robot-assisted laparoscopic prostatectomy (RALP) has emerged as the most common treatment for localized prostate cancer. With improved surgical precision, RALP has produced hope of improved potency rates, especially with the advent of nerve-sparing and other modified techniques. However, erectile dysfunction (ED) remains a significant problem for many men regardless of surgical technique. To identify the functional outcomes of robotic versus open and laparoscopic techniques, new robotic surgical techniques and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Traditional IIEF-15 and EPIC questionnaires are long and cumbersome to administer and currently most of the literature uses SHIM score in the preoperative setting and postoperative erection suitable for intercourse in the postoperative setting to categorize patients with ED post-RARP. 13 We developed two nomograms, one to be used in the preoperative period and one in the immediate postoperative period. As recommended by Royston et al, we used several statistical tools for internal and external validation; CIF curves at different levels of the prognostic index and different levels of the single prognostic factors, hazard ratios across risk groups, ROC curves and AUCs, calibration plots 20 while the other 2 used only calibration plots in their validation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional IIEF-15 and EPIC questionnaires are long and cumbersome to administer and currently most of the literature uses SHIM score in the preoperative setting and postoperative erection suitable for intercourse in the postoperative setting to categorize patients with ED post-RARP. 13 We developed two nomograms, one to be used in the preoperative period and one in the immediate postoperative period. As recommended by Royston et al, we used several statistical tools for internal and external validation; CIF curves at different levels of the prognostic index and different levels of the single prognostic factors, hazard ratios across risk groups, ROC curves and AUCs, calibration plots 20 while the other 2 used only calibration plots in their validation.…”
Section: Discussionmentioning
confidence: 99%
“…The primary end point of EF is defined as the ability to penetrate and satisfactorily complete intercourse with or without PDE5 inhibitor usage in more than half of the attempts. 12,13…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whelan et al demonstrated that RALP provides better potency outcomes than an open radical prostatectomy but only in high-volume centers with experienced surgeons. [ 9 ] Consequently, our patient pool was chosen from a single high-volume center, operated by the same surgeon who has done >250 RALP's per year for the last 10 years. In a larger reported series, Ficarra et al summarized that the incidence of erectile function recovery after RALP at 1 year was 70% (54%–90%).…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Evidence points toward some factors as being associated with better outcomes, such as high-volume centers, bilateral nerve sparing, absence of lateral traction and bleeding, ideal plane of dissection, athermal technique, and a single experienced surgeon. [ 3 4 5 6 7 8 9 ] However, what is lacking is a standardized measurable intraoperative method of scaling and grading the nerve sparing, taking into consideration all these factors simultaneously to enable physicians to preemptively predict the potency outcome postoperatively.…”
Section: Introductionmentioning
confidence: 99%